Characteristics of Mothers Undergoing Caesarean Section at Swadana Tarutung Regional General Hospital - Urhuhe Dena Siburian; Paruhum Tiruon Ritonga (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Caesarean section (CS) delivery remains high in referral hospitals and requires continuous monitoring to support maternal health service planning. This study aimed to describe the characteristics of mothers undergoing CS at Swadana Tarutung Regional General Hospital in 2024. This study employed a retrospective descriptive design with a cross-sectional approach. The population consisted of 1,250 mothers who delivered by CS from January to December 2024. A total of 303 medical records were selected using systematic random sampling. Secondary data were obtained from medical records and delivery registers, including maternal age, gravidity, parity, education, and occupation. Data were analyzed using SPSS version 23.0. Univariate analysis was used to describe frequency distributions, while the Chi-square goodness-of-fit test was used to assess differences in the distribution of each characteristic, with a significance level of p < 0.05. The results showed that most mothers undergoing CS were aged 20–35 years (75.2%), multigravida (41.4%), multipara (50.8%), had completed senior high school education (66.7%), and worked as farmers (39.3%). The distribution of maternal age, education, occupation, gravidity, and parity among CS cases showed statistically significant differences. These findings indicate that CS cases were concentrated in certain maternal characteristic groups. However, because this study did not include non-CS deliveries as a comparison group, the findings should not be interpreted as determinants of CS incidence. Future studies are recommended to include both CS and non-CS deliveries and analyze clinical indications to identify factors associated with CS delivery Keywords: Caesarean section, maternal characteristics, gravidity, parity, medical records